Islamic Religious Education Learning Model in Preventing Radicalism Among Students - Abdul Hamid; Mutawakkil; Nurhayati (Formosa Journal of Sustainable Research, 2023)
The purpose of this study was to describe the learning model of Islamic religious education in preventing radicalism among students of the Tadulako University FKIP study program, and the strategy of PAI lecturers to create a campus that is religious, inclusive, moderate and peace-loving. This type of research is descriptive-qualitative. The results of this study are that the PAI learning model in preventing radicalism in students is very helpful in minimizing and preventing radicalism. Even though radicalism in students reaches 10% to 25% it is still categorized as very low. Substantial efforts have been made by PAI lecturers in preventing radicalism in students by developing Islamic Islamic education learning models such as; direct learning, contextual, problem-based, and cooperative learning